2005
DOI: 10.1038/sj.bjc.6602715
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of osteopontin expression in early-stage non-small-cell lung cancer

Abstract: Osteopontin (OPN) is a multifunctional protein, which has recently been shown to be linked to tumorigenesis, progression and metastasis in different malignancies. Since non-small-cell lung cancer (NSCLC)'s prognosis remains bad, with few predictors of outcome, the purpose of this study was to evaluate if OPN might be involved in NSCLC's biology and therefore represent a prognostic marker and a target for new therapeutic trials. Immunohistochemistry was used to detect OPN expression, evaluated as percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 23 publications
(25 reference statements)
1
62
1
5
Order By: Relevance
“…A further 2 studies were excluded [one focused on the association between OPN and bone metastases (17), whereas the other provided limited data on HR and 95% CI (18) and the authors were unavailable for more detailed information]. In addition, after performing an in-depth check of the literature, we found that the same cohort was enrolled in two reports (19,20) and only considered the study by Donati et al (19), which had a larger sample size and included more detailed information. Finally, 6 studies were considered eligible for the meta-analysis, comprising a total of 776 patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further 2 studies were excluded [one focused on the association between OPN and bone metastases (17), whereas the other provided limited data on HR and 95% CI (18) and the authors were unavailable for more detailed information]. In addition, after performing an in-depth check of the literature, we found that the same cohort was enrolled in two reports (19,20) and only considered the study by Donati et al (19), which had a larger sample size and included more detailed information. Finally, 6 studies were considered eligible for the meta-analysis, comprising a total of 776 patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons for this variation is that stage I NSCLC includes populations with a different grade of malignancy [4]. This observation underlines how important it is to identify novel pathological parameters in addition to disease stage and, most of all, new biological markers, in order to add further prognostic information, select high-risk patients for aggressive adjuvant treatments [5].…”
Section: Introductionmentioning
confidence: 98%
“…[11,12,13,14,15,16]. A growing body of clinical evidence supports a role for OPN as a potential prognostic indicator for human cancers including lung, esophagus, prostate, ovarian, hepatocellular and breast cancers [17,18,19,20,21,22,23,24]. Several studies have reported that OPN mRNA, protein expression and plasma level are all closely correlated with invasion and metastasis of GC [26,27,28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical evidence suggests that OPN is a valuable prognostic indicator of various human cancers, including lung, esophagus, prostate, ovarian, hepatocellular and breast cancer [17,18,19,20,21,22,23,24]. For example, OPN mRNA overexpression was associated with portal-vein invasion, and had the potential for predicting early recurrence and short patient survival in early-stage hepatocellular cancer [22].…”
Section: Introductionmentioning
confidence: 99%